2018
DOI: 10.3892/ijmm.2018.3428
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-327 regulates cardiac hypertrophy and fibrosis induced by pressure overload

Abstract: MicroRNA (miRNA/miR) dysregulation has been reported to be fundamental in the development and progression of cardiac hypertrophy and fibrosis. In the present study, miR-327 levels in fibroblasts were increased in response to cardiac hypertrophy induced by transverse aortic constriction with prominent cardiac fibrosis, particularly when compared with the levels in unstressed cardiomyocytes. In neonatal rat cardiac fibroblasts, induced expression of miR-327 upregulated fibrosis-associated gene expression and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…In vivo silencing of miR-125b could rescue Ang-II-induced cardiac fibrosis [ 54 ]. Moreover, overexpression of miR-327 promoted Ang-II-induced differentiation of cardiac fibroblasts into myofibroblasts [ 65 ], while let-7i miRNAs exhibited opposite effects [ 86 ].…”
Section: The Functions Of Mirnas In Cardiac Fibrosis-related Signalin...mentioning
confidence: 99%
“…In vivo silencing of miR-125b could rescue Ang-II-induced cardiac fibrosis [ 54 ]. Moreover, overexpression of miR-327 promoted Ang-II-induced differentiation of cardiac fibroblasts into myofibroblasts [ 65 ], while let-7i miRNAs exhibited opposite effects [ 86 ].…”
Section: The Functions Of Mirnas In Cardiac Fibrosis-related Signalin...mentioning
confidence: 99%
“…During cardiac hypertrophy, the regulation of cardiac fibroblasts by Ang II and other factors results in excessive proliferation and the production of excessive quantities of fibrin, which leads to cardiac fibrosis and can further aggravate cardiac hypertrophy (26)(27)(28). Therefore, inhibition of the proliferation and fibrosis of cardiac fibroblasts may serve as a viable strategy for treating cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, Ji et al (Ji et al, 2018) reported that the miR-327 expression was the highest in fibrotic heart tissue induced by transverse aortic constriction (TAC) in mice, and downregulation of miR-327 inhibited cardiac hypertrophy and fibrosis by targeting integrin β3(ITGB3). In addition, some studies reported that excessive ROS can activate MMPs, which play an important role in LV remodeling (Hori and Nishida, 2009;Baghirova et al, 2016).…”
Section: Discussionmentioning
confidence: 99%